The nature of teacher anxiety in English-medium tertiary education in Saudi Arabia - Alruwaili, Shatha (Frontiers in Education, 2023)
While student anxiety, and factors affecting it, have been quite widely studied, this is less true of teacher anxiety, especially at tertiary level. Furthermore, inventories for the measurement of teacher anxiety seem more disparate and less standardised than those for student anxiety. These considerations prompted the present study which aimed to reveal just how anxious tertiary level teachers really are, and what factors, both demographic and situational, are associated with their anxiety, in a relatively neglected non-Western context. A comprehensive questionnaire, was employed, combining items from a number of rather different previous teacher anxiety questionnaires, and applied to 88 university teachers at a Saudi university post COVID. Although anxiety was judged to have increased due to COVID, it still remained below the midpoint of the scale in absolute terms. While age and level of academic qualification were negatively related to overall teaching anxiety, experience, training, gender, and reported general trait anxiety were not. Notably features of the students (e.g. low ability or home difficulties) and of the administration (e.g. imposing high workload and unsuitable class sizes) generated relatively stronger anxiety compared with features in the hands of the teachers themselves (e.g. speaking in front of a class or answering student questions).